Business Process Management Culture in Public Administration and Its Determinants - Ingo Kregel; Bettina Distel; André Coners (Business & Information Systems Engineering, 2021)
Public administration institutions increasingly use business process management (BPM) to innovate internal operations, increase process performance and improve their services. Research on private sector companies has shown that organizational culture may impact an organization's BPM and this culture is often referred to as BPM culture. However, similar research on public administration is yet missing. Thus, this article assesses BPM culture in Germany's municipal administration. 733 online survey responses were gathered and analyzed using MANOVA and follow-up discriminant analyses to identify possible determinants of public administration's BPM culture. The results indicate that the employees' professional experience and their responsibility influence the assessment of BPM culture, as does the size of a municipality. Based on these findings, the article proposes testable relationships and an agenda for further research on BPM culture in public administration.
Keywords: 000; Business process management; Organizational culture; BPM culture; Explorative research; Public administration; Local government